Novel indolin-2-one-substituted methanofullerenes bearing long n-alkyl chains: synthesis and application in bulk-heterojunction solar cells - Romanova, Irina P.; Bogdanov, Andrei V.; Izdelieva, Inessa A.; Trukhanov, Vasily A.; Shaikhutdinova, Gulnara R.; Yakhvarov, Dmitry G.; Latypov, Shamil K.; Mironov, Vladimir F.; Dyakov, Vladimir A.; Golovnin, Ilya V.; Paraschuk, Dmitry Yu.; Sinyashin, Oleg G. (Beilstein Journal of Organic Chemistry, 2014)
An easy, high-yield and atom-economic procedure of a C60 fullerene modification using a reaction of fullerene C60 with N-alkylisatins in the presence of tris(diethylamino)phosphine to form novel long-chain alkylindolinone-substituted methanofullerenes (AIMs) is described. Optical absorption, electrochemical properties and solubility of AIMs were studied. Poly(3-hexylthiophene-2,5-diyl) (P3HT)/AIMs solar cells were fabricated and the effect of the AIM alkyl chain length and the P3HT:AIM ratio on the solar cell performance was studied. The power conversion efficiencies of about 2% were measured in the P3HT/AIM devices with 1:0.4 P3HT:AIM weight ratio for the AIMs with hexadecyl and dodecyl substituents. From the optical and AFM data, we suggested that the AIMs, in contrast to [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), do not disturb the P3HT crystalline domains. Moreover, the more soluble AIMs do not show a better miscibility with the P3HT crystalline phase.
Keywords: bulk heterojunction; fullerenes; isatin; phosphorus; photovoltaics